TINGKAT PENDAPATAN DAN NILAI TAMBAH USAHATANI PADI PADA PETANI PESERTA PROGRAM PASCAPANEN DI KABUPATEN LAMPUNG TIMUR - Anggun Psikiatri; Sudarma Widjaya; Indah Nurmayasari (Lampung University, 2015)
This study aims to analyze level of income of farmerparticipants and non-participantsof ricepostharvest program, and post-harvest value-added of rice.The survey was conducted in Raman Fajar Villageas the program participantand Ratna Daya Villageas non-participant. From each sampled village, two farmer groups were selectedpurposively. The number of respondents were 25 farmers from each farmer group. Data were collectedthrough interviews using questionnaires and analyzed using tabulation and t-test. The results showed that 1) the average rice farming income of farmers participating in the program is smaller than that of nonparticipants, 2) there is asignificant difference in rice farm income between farmer participants and nonparticipantsin rainy season but there is no difference in dry season, 3) the use of rice Milling Unit (RMU) gives a positive value-added to farmers participating in the program in Raman Fajar Village Raman Utara Subdistrict of East Lampung Regency. Key words : paddy farmers, post-harvest program, income, value-added